GMJ 2020
DOI: 10.31661/gmj.v9i0.1645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Facilitators and Barriers to Implementing Evidence-Based Practice in the  Health Services: A Systematic Review

Abstract: Background: Evidence-based practice (EBP) is an ambition for health service administrators. We aimed to systematically review the major relevant articles in case of barriers and facilitators to implementing evidence-based practice in health services. Methods and Materials: The type of study was a systematic review. We searched the libraries and online sources such as PubMed, MEDLINE, Wiley, EMBASE, ISI Web of Knowledge, Scopus, Science Direct, Cochrane Library, and Google scholar. We used keywords included “Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
1
17
0
2
Order By: Relevance
“…As in previous studies, this positive relationship has been expressed to some extent. [ 8 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in previous studies, this positive relationship has been expressed to some extent. [ 8 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 32 ] However, the studies on medical students showed increased EBP awareness and critical appraisal ability of articles after participating in the evidence-based training workshop. [ 8 13 14 15 ] The observed difference can be sufficient to hold various EBP training workshops and MPH courses for students. Having these multiple courses play a significant role in promoting EBP acceptance and awareness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is important to note that the IF training program was developed within settings that are well resourced compared to those less resourced (e.g., low- and middle-income countries), and barriers to implementation may differ ( Ayoubian et al, 2020 ). To address the application of IF in these settings, additional emphasis on political and structural formative evaluation thorough documentation of recipient characteristics, and further potential adaptations of the innovation should be expanded in the IF training content.…”
Section: Limitationsmentioning
confidence: 99%